True hermaphroditism: A nightmare for an adult - Ranjit B. Vishwakarma; Venkat A. Gite; Vivek Shaw; Shashank Sharma (Current Urology)
Abstract. The disorder of sex development is a rare disorder that usually occurs in early childhood. As adults, those with disorder of sexual development present with gynecomastia, primary amenorrhea, and primary infertility, which often causes great psychological impact. We report a unique case of a male adult hermaphrodite presenting with hematometra and hematosalpinx. Early management including psychiatry counseling, gender reassignment, and surgery is essential. Our patient underwent müllerian tissue removal with phallus reconstruction.